Promosi Kesehatan Berbasis Rumah Sakit sebagai Upaya Meningkatkan Pengetahuan dan Literasi Masyarakat untuk Melakukan Vaksinasi Covid-19 - Bayu Anggileo Pramesona; Suharmanto Suharmanto; Dyah Wulan Sumekar Rengganis Wardani (Jurnal Pengabdian Kesehatan Komunitas, 2021)
Background The low level of knowledge and culture of literacy as well as the spread of hoax news related to vaccines are - risk factors for the low participation of the community in carrying out Covid-19 vaccinations. The purpose of this activity is to increase public knowledge and literacy to carry out Covid-19 vaccinations through a hospital-based health promotion program. The Methods this hospital-based health promotion program used a lecture method and interactive discussion with 102 patients and hospital visitors at Mayjend HM Ryacudu Government Hospital Kotabumi, North Lampung on 27 July 2021. The promotional media used were Powerpoints, banners and standing banners about Covid-19 vaccination. Knowledge measurement was carried out by giving pre-test and post-test about Covid- 19 vaccination before and after the activity. The results of the evaluation showed an increase in the average knowledge of patients and hospital visitors by 22.1% after health promotions regarding Covid-19 vaccination. The highest increase in knowledge occurred in terms of knowledge about the types of Covid-19 vaccines, which was 32.3% when compared between pre and post health promotion, followed by knowledge about monitoring KIPI (Follow-up Events After Immunization/ FEAI) (30.4%), safety and efficacy of Covid-19 vaccines (27.5%), the definition of vaccination (23.6%), the purpose of the Covid-19 vaccination (16.7%), the halal issue of the Covid-19 vaccine (14.7%), and the benefits of the Covid-19 vaccination (9.8%). In conclusion, hospital-based health promotion has been proven to increase public knowledge and literacy related to Covid-19 vaccination. The role of the hospital is very central in efforts to accelerate the Covid-19 vaccination in Indonesia. Counseling to the community, especially targets that are rarely visited, for example in Islamic boarding schools, schools, etc., need to be improved so that the information obtained can be more evenly distributed. ABSTRAK Latar Belakang Rendahnya pengetahuan dan budaya literasi serta berita hoaks yang menyebar terkait vaksin menjadi faktor risiko rendahnya partisipasi masyarakat untuk melakukan vaksinasi Covid-19. Tujuan kegiatan ini yaitu meningkatkan pengetahuan dan literasi masyarakat untuk melakukan vaksinasi Covid-19 melalui promosi kesehatan berbasis rumah sakit. Metode Program promosi kesehatan berbasis RS ini menggunakan metode ceramah dan diskusi interaktif terhadap 102 pasien dan pengunjung rumah sakit (RS) di RSD Mayjend HM Ryacudu Kotabumi, Kabupaten Lampung Utara pada 27 Juli 2021. Media promosi yang digunakan berupa Powerpoint, spanduk dan standing banner tentang vaksinasi Covid-19. Pengukuran pengetahuan dilakukan dengan memberikan pre-test dan post-test tentang vaksinasi Covid-19 sebelum dan setelah kegiatan. Hasil evaluasi menunjukkan terjadi peningkatan rata-rata pengetahuan pasien dan pengunjung RS sebesar 22.1% setelah dilakukan promosi kesehatan tentang vaksinasi Covid-19. Peningkatan pengetahuan tertinggi terjadi dalam hal pengetahuan tentang jenis-jenis vaksin Covid-19 yaitu sebesar 32.3% jika dibandingkan antara pre dan post promosi kesehatan, kemudian diikuti pengetahuan tentang pemantauan KIPI (30.4%), keamanan dan efikasi vaksin Covid-19 (27.5%), definisi vaksinasi (23.6%), tujuan vaksinasi Covid-19 (16.7%), kehalalan vaksin Covid-19 (14.7%), serta manfaat vaksinasi Covid-19 (9.8%). Kesimpulan Promosi kesehatan berbasis RS terbukti dapat meningkatkan pengetahuan dan literasi masyarakat terkait vaksinasi Covid-19. Peran RS sangat sentral dalam upaya percepatan vaksinasi Covid-19 di Indonesia. Penyuluhan kepada masyarakat khususnya target sasaran yang jarang dikunjungi misal di pesantren, sekolah-sekolah, dan lain sebagainya perlu ditingkatkan sehingga informasi yang didapatkan dapat lebih merata.